Memory formation for trace fear conditioning requires ubiquitin-proteasome mediated protein degradation in the prefrontal cortex - Reis, David S.; Jarome, Timothy J.; Helmstetter, Fred J. (Frontiers in Behavioral Neuroscience, 2013)
The cellular mechanisms supporting plasticity during memory consolidation have been a subject of considerable interest. De novo protein and mRNA synthesis in several brain areas are critical, and more recently protein degradation, mediated by the ubiquitin-proteasome system (UPS), has been shown to be important. Previous work clearly establishes a relationship between protein synthesis and protein degradation in the amygdala, but it is unclear whether cortical mechanisms of memory consolidation are similar to those in the amygdala. Recent work demonstrating a critical role for prefrontal cortex (PFC) in the acquisition and consolidation of fear memory allows us to address this question. Here we use a PFC-dependent fear conditioning protocol to determine whether UPS mediated protein degradation is necessary for memory consolidation in PFC. Groups of rats were trained with auditory delay or trace fear conditioning and sacrificed 60 min after training. PFC tissue was then analyzed to quantify the amount of polyubiquibated protein. Other animals were trained with similar procedures but were infused with either a proteasome inhibitor (clasto-lactacystin β-lactone) or a translation inhibitor (anisomycin) in the PFC immediately after training. Our results show increased UPS-mediated protein degradation in the PFC following trace but not delay fear conditioning. Additionally, post-training proteasome or translation inhibition significantly impaired trace but not delay fear memory when tested the next day. Our results further support the idea that the PFC is critical for trace but not delay fear conditioning and highlight the role of UPS-mediated degradation as critical for synaptic plasticity.